2021
DOI: 10.3390/jpm11121332
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Retroviral Elements in Human Development and Central Nervous System Embryonal Tumors

Abstract: Human endogenous retroviruses (HERVs), which are critical to normal embryologic development and downregulated during normal maturation, have been implicated in a variety of cancers. Abnormal persistent production of HERVs has been suggested to play a role in oncogenesis and to confer stem cell properties to cells. We recently demonstrated that the most recently incorporated HERV element (HERV-K HML-2) has been associated with the pathogenesis of the embryonal atypical teratoid rhabdoid tumor (AT/RT), shifting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A key epigenetic regulator, the chromatin remodeling SWItch/Sucrose Non-Fermentable (SWI/SNF) complex, plays an important role in the transcriptional activation of stress-response genes that are often activated during aging [ 63 ] . In addition, the expression of endogenous retroviruses is tightly spatially and temporally regulated during development, and they are normally downregulated as cells differentiate and mature [ 11 , 64 ] . Therefore, endogenous retroviral expression may be an excellent treatment target for neurodevelopmental tumors, neurodegenerative diseases, and senescence, and current treatments, e.g., anti-retroviral drugs and ERV targeting short hairpin RNAs (shRNAs), designed to abrogate their expression should potentially be explored [ 10 , 26 , 65 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key epigenetic regulator, the chromatin remodeling SWItch/Sucrose Non-Fermentable (SWI/SNF) complex, plays an important role in the transcriptional activation of stress-response genes that are often activated during aging [ 63 ] . In addition, the expression of endogenous retroviruses is tightly spatially and temporally regulated during development, and they are normally downregulated as cells differentiate and mature [ 11 , 64 ] . Therefore, endogenous retroviral expression may be an excellent treatment target for neurodevelopmental tumors, neurodegenerative diseases, and senescence, and current treatments, e.g., anti-retroviral drugs and ERV targeting short hairpin RNAs (shRNAs), designed to abrogate their expression should potentially be explored [ 10 , 26 , 65 ] .…”
Section: Discussionmentioning
confidence: 99%
“…AT/RT has a bimodal distribution of disease in both young and older individuals, highlighting the possibility of endogenous retroviral involvement in tumors occurring later in life [62] . A key epigenetic regulator, the chromatin remodeling SWItch/Sucrose Non-Fermentable (SWI/SNF) complex, plays an important role in the transcriptional activation of stress-response genes that are often activated during aging [63] . In addition, the expression of endogenous retroviruses is tightly spatially and temporally regulated during development, and they are normally downregulated as cells differentiate and mature [11,64] .…”
Section: Discussionmentioning
confidence: 99%
“…Within this large, heterogeneous category of CNS primary tumors, epigenetic profiling represents an additional means of investigating these discrepancies and reconciling them. For example, alterations in the SWI/SNF pathway have been found in gliomagenesis as well as aberrant ERV expression [14,15,17,24,25,33,146,147]. This targeted treatment based upon individual tumor profiling may provide a unique therapeutic opportunity for tumors that have historically been treated by non-specific means, which harbor their own potential for inducing tumorigenesis, such as chemotherapy and radiation [148,149].…”
Section: Gliomas Glioneuronal Tumors and Neuronal Tumorsmentioning
confidence: 99%
“…Further, we have recently shown that LOF of SWI/SNF proteins can lead to the activation of endogenous retroviruses (ERVs) such as human endogenous retrovirus K (HERV-K, sub-type HML-2) [10]. Normally, ERV expression is tightly spatially and temporally controlled during development, and its expression is significantly downregulated as cells differentiate and mature; therefore, ERV expression provides an excellent target for tumor treatment [10][11][12][13][14][15][16][17]. Potential mechanisms that allow for aberrant expression of ERVs, such as LOF of the SWI/SNF complex, provide a unique opportunity for a combinatorial approach to the treatment of tumors with few targeted treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Human endogenous retroviruses (HERVs) are remnants of ancient infection by retroviruses, comprising nearly 8% of the human genome (Deniz et al, 2018; Durnaoglu et al, 2021a; Geis and Goff, 2020; Groh and Schotta, 2017; Liu et al, 2014; Mao et al, 2021). Whereas most HERVs are permanently inactivated by accumulated mutations or strongly suppressed by epigenetic machineries, some of the activation-competent copies of HERVs may play critical roles in a wide variety of human diseases, including various malignancies, autoimmune diseases, and neurological disorders (Babaian and Mager, 2016; Doucet-O’Hare et al, 2021). Non-physiological reactivation of HERVs may be caused by malnutrition, exposure to environmental toxicants, or impaired health conditions (Sakurai et al, 2019; Sharif et al, 2013; Shioda et al, 2022).…”
Section: Introductionmentioning
confidence: 99%